2007
DOI: 10.1038/sj.leu.2404882
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable leukemogenic potency and quality of a constitutively active neurotrophin receptor, ΔTrkA

Abstract: Neurotrophins and their receptors play a key role in neurogenesis and survival. However, we and others have recently obtained evidence for a potential involvement of this receptor system in leukemia. To investigate mechanisms underlying the leukemogenic potential of activated neurotrophin receptor signaling, we analyzed in vivo leukemogenesis mediated by DTrkA, a mutant of TRKA (tropomyosin-related kinase A) isolated from a patient with acute myeloid leukemia (AML). Retroviral expression of DTrkA in myeloid 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 46 publications
2
40
0
Order By: Relevance
“…To study whether naïve T cells are also resistant to transformation, HSCs/HPCs from three C57BL/6 Ly5.1 mice were transduced with the gammaretroviral vector SF91-DTrkA expressing an oncogenic, constitutively active form of TrkA 8 or with MP91-eGFP as a control vector (Supplementary Figure S1) and then transplanted into five sublethally irradiated Rag-1 À / À Ly5.2 mice (Figure 1a). In our previous study, 7 DTrkA was the most potent oncogene, with which we had shown resistance of memory T cells to development of MTCLs.…”
Section: Resultsmentioning
confidence: 99%
“…To study whether naïve T cells are also resistant to transformation, HSCs/HPCs from three C57BL/6 Ly5.1 mice were transduced with the gammaretroviral vector SF91-DTrkA expressing an oncogenic, constitutively active form of TrkA 8 or with MP91-eGFP as a control vector (Supplementary Figure S1) and then transplanted into five sublethally irradiated Rag-1 À / À Ly5.2 mice (Figure 1a). In our previous study, 7 DTrkA was the most potent oncogene, with which we had shown resistance of memory T cells to development of MTCLs.…”
Section: Resultsmentioning
confidence: 99%
“…In more than half of the mice (5 of 9) that received transplants of SF91-⌬TrkA high -transduced HSCs/HPCs, we observed a hyperacute myeloid proliferation, previously termed "transient leukemia" (TL), 10 with a latency of less than 12 days (Table 1). This TL was characterized by significant spleen enlargement (up to 4.8 g; Table S1C).…”
Section: Oncogenes Transform Primary Murine Hscs/hpcsmentioning
confidence: 95%
“…10 The vector is referred to as SF91-⌬TrkA. The vector MP91-wPRE was shown to support high transgene expression in mouse transplantation models.…”
Section: Retroviral Vectors/cloningmentioning
confidence: 99%
See 2 more Smart Citations